Religious Moderation of Formal and Informal: Its Implementation and Relevance in Countering Radicalism in Indonesia - Witro, Doli (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2024)
This article offers a strategy to instill the values of religious moderation in students through Islamic education as a formal application of religious moderation. On the other hand, in the practice of social life, many local wisdoms are owned by communities in various regions of Indonesia, which have similarities and can support indicators of religious moderation. Implementation in this form is said to be a form of informal application of religious moderation. This article aims to highlight the application of religious moderation in Indonesia formally through Islamic education and informally through local wisdom that is part of the customs and culture of Indonesian society. This article is a literature research study using the grounded theory approach method. The data used is qualitative and analyzed using Miles et al.’s qualitative data analysis techniques, namely data condensation, data presentation, and conclusion drawing. This study found that to give birth to a moderate generation, it is necessary to develop Islamic education by using religious moderation as a paradigm of religious moderation formally. In addition to formal forms, the application of religious moderation must also be supported by local wisdom embodied in the culture and customs of the people in each region in Indonesia as a form of informal application of religious moderation. This research contributes to stemming the radicalization of religion (Islam) that occurs in schools (educational institutions) while disseminating the value of religious moderation following the character of Indonesian Islam to students. In addition, it also contributes to preventing tension and conflict in the community, so a cultural approach is needed through local wisdom that has messages from local ancestors about peace.